2012
DOI: 10.1080/09540121.2012.701713
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination, social support, and perceived stress among people living with HIV/AIDS in China

Abstract: Perceived stress among people living with HIV/AIDS (PLWH) was associated with severe mental health problems and risk behaviors. Discrimination toward PLWH in China is prevalent. Both perceived discrimination and social supports are determinants of the stress level among PLWH. Psychological support services for PLWH in China are scarce. It is unknown whether social support is a buffer between the perceived discrimination and perceived stress. With written consent, this study surveyed 258 PLWH recruited from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 59 publications
4
30
0
4
Order By: Relevance
“…The measures used have been previously tested in Chinese populations and have shown strong reliability and validity [7,50,51]. …”
Section: Methodsmentioning
confidence: 99%
“…The measures used have been previously tested in Chinese populations and have shown strong reliability and validity [7,50,51]. …”
Section: Methodsmentioning
confidence: 99%
“…Depression among PLWH is largely influenced by the social environment. Perceived HIV-related social discrimination diminishes effectiveness of HIV prevention and care programs and quality of life among PLWH (Earnshaw and Quinn, 2012); it is associated with perceived stress, maladjustments and depression symptoms among PLWH (Pakenham and Rinaldis, 2002;Riggs et al, 2007;Su et al, 2009;Thompson et al, 1996;Wingood et al, 2007). Other studies have shown that perceived social support is significantly associated with effective adjustment to problems related to HIV/AIDS (Friedland et al, 1996;Leserman et al, 1999;Pakenham et al, 1994).…”
Section: Introductionmentioning
confidence: 90%
“…A manutenção da resiliência implica no enfrentamento de dificuldades e possibilita a superação de adversidades e situações potencialmente p.6 • Rev enferm UERJ, Rio de Janeiro, 2017; 25:e17040. [18][19][20][21] . E por fim, o DE risco de sentimento de impotên-cia esteve presente em 7(6,19%), apresentando como fatores de risco o conhecimento deficiente do paciente sobre a doença, e o fato desta ser uma doença estigmatizada.…”
unclassified